Long‐term microbiota and virome in a Zürich patient after fecal transplantation against Clostridium difficile infection. Issue 1 (10th June 2016) - Broecker, Felix; Klumpp, Jochen; Moelling, Karin
Abstract : Fecal microbiota transplantation (FMT) is an emerging therapeutic option for Clostridium difficile infections that are refractory to conventional treatment. FMT introduces fecal microbes into the patient's intestine that prevent the recurrence of C. difficile, leading to rapid expansion of bacteria characteristic of healthy microbiota. However, the long‐term effects of FMT remain largely unknown. The C. difficile patient described in this paper revealed protracted microbiota adaptation processes from 6 to 42 months post‐FMT. Ultimately, bacterial communities were donor similar, suggesting sustainable stool engraftment. Since little is known about the consequences of transmitted viruses during C. difficile infection, we also interrogated virome changes. Our approach allowed identification of about 10 phage types per sample that represented larger viral communities, and phages were found to be equally abundant in the cured patient and donor. The healthy microbiota appears to be characterized by low phage abundance. Although viruses were likely transferred, the patient established a virome distinct from the donor. Surprisingly, the patient had sequences of algal giant viruses (chloroviruses) that have not previously been reported for the human gut. Chloroviruses have not been associated with intestinal disease, but their presence in the oropharynx may influence cognitive abilities. The findings suggest that the virome is an important indicator of health or disease. A better understanding of the role of viruses in the gut ecosystem may uncover novel microbiota‐modulating therapeutic strategies.